Does meeting the Milan criteria at the time of recurrence of hepatocellular carcinoma after curative resection have an impact on prognosis?. Issue 3 (1st November 2018) - Kim, Hyo‐Sin; Yi, Nam‐Joon; Kim, Jong Man; Hong, Suk Kyun; Kwon, Choon Hyuck David; Joh, Jae‐Won; Lee, Kwang‐Woong; Suh, Kyung‐Suk
Abstract : Background: The survival outcomes of recurrent hepatocellular carcinoma (HCC) after curative resection remain unclear due to lack of clear basis for the selection of treatment option. We investigated overall survival (OS) after intrahepatic recurrence and re‐recurrence free survival (rRFS) of the patients with recurrent HCC, and whether Milan criteria (MC) status at resection and recurrence impacts on OS and rRFS. Method: We enrolled 959 patients who experienced recurrence after primary hepatic resection for HCC. We divided the cohort into four groups according to MC at two periods: IN‐rIN MC (HCC within MC at the time of resection‐recurrence within MC), IN‐rOUT MC (HCC within MC at the time of resection‐recurrence outside MC), OUT‐rIN MC (HCC outside MC at the time of resection‐recurrence within MC), and OUT‐rOUT MC (HCC outside MC at the time of resection‐recurrence outside MC). Results: In the entire cohort, 1‐, 3‐, and 5‐year OS after recurrence was 81.0%, 55.7%, and 45.8%, respectively, while rRFS was 63.7%, 46.1%, and 42.0%, respectively. The IN‐rIN MC group had the best outcomes (5‐year OS and rRFS, 54.5% and 45.7%, respectively). The IN‐rOUT and OUT‐rIN MC groups had better 5‐year OS outcomes than the OUT‐rOUT MC group (46.5%, 38.6%, and 24.8%, respectively; P < 0.05). However, 5‐year rRFS did not differ among the three groups (37.5%, 36.6%, and 31.9%, respectively; P > 0.05). Conclusion: Survival after first recurrence following curative primary resection for HCC was affected by MC at both time of resection and recurrence. Both the IN‐rOUT and OUT‐rIN MC groups with similar survival outcomes can be saved via curative treatment.